Incidence and risk factors for cervical lesions in patients with rheumatoid arthritis under the current pharmacologic treatment paradigm. Issue 4 (4th July 2017) - Kaito, Takashi; Ohshima, Shirou; Fujiwara, Hiroyasu; Makino, Takahiro; Yonenobu, Kazuo; Yoshikawa, Hideki
Abstract: Objective : To elucidate the incidence and risk factors for cervical lesions in patients with rheumatic arthritis (RA) under the current pharmacologic treatment paradigm. Methods : Of patients with RA onset after 2000, 151 who introduced biologic agents (BAs) because of high disease activity and underwent cervical radiography more than 5 years after onset were included. Incidence of those with cervical lesions and predictors of cervical lesions were analyzed. Mean disease duration was 8.5 years. The radiographic definitions of cervical lesions were as follows: atlantoaxial subluxation (AAS), atlantodental interval >3 mm; vertical subluxation (VS), Ranawat value <13 mm; and subaxial subluxation (SS), and listhesis >2 mm. Results : Radiographic evaluation indicated AAS in 43 cases (28%), VS in 10 (7%), and SS in 6 (4%). The incidence of those with any cervical lesion was 32% (48/151). Univariate analysis showed that disease duration, time from onset to BA use, and onset before 2005 were significant predictors of cervical lesions, while multivariate regression analysis showed that disease duration and Steinbrocker stage were predictors. Conclusion : The incidence of cervical lesions in patients with RA onset after 2000 was still high (32%). In addition, disease duration and Steinbrocker stage were predictors of cervical lesions.